A joinder to Keyan Tomaselli’s "The 2022 Copyright Amendment Bill: Implications for the South African universities’ Research Economy" - Sadulla Karjiker (Communicare)
In his article “The 2022 Copyright Amendment Bill: Implications for the South African universities’ research economy”, Prof Keyan Tomaselli has focused on the implications of the Copyright Amendment Bill (the “Bill”) for academic publication.1 His article seeks to engage with the Bill at a level that proponents of the Bill simply refuse to do (or have displayed an unwillingness, or inability, to do); they have been allowed to lobby for and defend the Bill at the level of rhetoric.2 While Tomaselli’s contribution to the debate on the Bill focuses on the possible consequences for academic publication, his article brings together some wider concerns as regards the credibility of the process that has led up to the Bill.